Development of Adaptive Excitation Control Equipment for Synchronous Generator - YANG Dongxin; LIU Songbai; FENG Bing (Kongzhi Yu Xinxi Jishu)
Diesel-generator system of diesel locomotive is a kind of inertial system with wide-range speed governing and voltage regulating and its operation condition is complex. It developed an excitation control equipment with an adaptive algorithm based on the least square method to satisfy various operational demands of diesel locomotive and performed the load characteristic automatic regulation research based on no-load characteristic of synchronous generator. Actual operation results show that the excitation control equipment improves regulating accuracy and respond speed of the diesel locomotive excitation system, with simple and reliable algorithm.